Evaluation of fluocinolone acetonide 0.19 mg intravitreal implant in the management of birdshot retinochoroiditis. Issue 2 (26th November 2020) - Ajamil-Rodanes, Sofia; Testi, Ilaria; Luis, Joshua; Robson, Anthony G; Westcott, Mark; Pavesio, Carlos
Abstract : Purpose: To report treatment outcomes and efficacy of the fluocinolone acetonide 0.19 mg intravitreal implant (Iluvien) in controlling retinal and choroidal inflammation in 11 patients with birdshot retinochoroiditis. Methods: A single-centre, retrospective, interventional case series. The primary efficacy end point was improvement in vascular leakage on fluorescein angiography (FA), effect on cystoid macular oedema (CMO) and resolution of hypofluorescent lesions on indocyanine green angiography (ICGA); secondary measures were improvements on pattern and full-field electroretinogram (PERG; ERG) parameters. Safety outcome measures were intraocular elevation and cataractogenesis. Results: Fifteen eyes received Iluvien implant with an average follow-up of 31 months (range 12–36 months). Prior to the implant, 5 (33.3%) eyes had received dexamethasone intravitreal implant 0.7 mg (Ozurdex). FA showed evidence of vascular leakage in all eyes at baseline. Between month 6 and 12, FA showed that 73.4% of eyes had no leakage, this increased to 84.6% by month 24. Three eyes in our study had CMO at baseline. 6 months after Iluvien implant, all eyes achieved complete CMO resolution. One year after insertion of the implant, the characteristic hypofluorescent lesions on ICGA were unchanged in all cases. There was baseline ERG evidence indicating a high incidence of peripheral cone system dysfunction and most showed PERG evidence of macular dysfunction. Retinal function improved and macular function improved or was stable in the majority following treatment. Conclusions: The results show the possible therapeutic effect of Iluvien in the management of Birdshot-related vascular leakage, CMO and retinal dysfunction. However, choroidal lesions seem to persist with no detectable response to treatment.